INTEGRATION MODEL TPB AND PERCEIVED RISK OF INTENTION OF USE APPLICATIONS AND GAMES ONLINE FREEMIUM PAID VERSION: INDONESIAN STUDENTS CONTEXT - Harmanda Berima Putra; Nungki Pradita; Anwar Mansyur (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study examines how the Theory of Planned Behavior and perceived risk can affect the intention to switch users of free versions of freemium online applications and games to use paid versions of freemium online applications and games. Data was collected using an online questionnaire which was distributed to 226 students at several universities in Indonesia. This study was analyzed using Structural Equation Modeling with Amos. The results showed that attitude proved to have a positive effect on intention. Subjective norms proved to have a positive effect on perceived behavioral control and attitudes. Perceived behavioral control has a positive effect on attitudes and intentions. Subjective norms were not shown to have a negative effect on intentions. Perceived performance risk does not affect attitudes and intentions to use freemium paid versions of online applications and games.